Autocatalytic reactive flame retardants for rigid polyurethane foams - ÇAKMAKÇI, EMRAH; KAHRAMAN, MEMET VEZİR (ELSEVIER SCIENCE SA, 2021)
While technological progress is rapidly accelerating day by day, the demand for cutting-edge materials is also ever-growing. In terms of material chemistry, ingenious polymers and additives with superior properties are desired. To meet this need, in this study, we would like to present an innovative concept; autocatalytic reactive flame retardants (ACRFRs) for polyurethanes. In this work, we synthesized two different phosphorous and nitrogen containing flame retardants. They were characterized by FTIR and NMR techniques and were added into PUF formulations at different ratios (2.5, 5 and 10%). Their effects on the thermal, mechanical, flame retardancy and physical properties of the foams were investigated along with their catalytic performance. The synthesized ACRFRs displayed good catalytic activity, moderate flame retardancy (depending on the type and the concentration of the ACRFR). We believe more ACRFRs will be synthesized in future and find a place in industrial applications.
Keywords: Flame retardant; DOPO; Polyurethane foam; Autocatalytic; LOI; EPOXY-RESINS; PHOSPHORUS; HAZARDS; NANOPARTICLES; COMPOSITES; POLYOL